2019
DOI: 10.1002/dvdy.7
|View full text |Cite
|
Sign up to set email alerts
|

FoxA expression pattern in two polychaete species, Alitta virens and Platynereis dumerilii: Examination of the conserved key regulator of the gut development from cleavage through larval life, postlarval growth, and regeneration

Abstract: Background foxA orthologs are involved in various processes from embryo patterning to regulation of metabolism. Since foxA conserved role in the development of the gut of errant annelids has never been thoroughly studied, we used a candidate gene approach to unravel the molecular profile of the alimentary canal in two closely related nereid worms with a trochophore‐type lecithotrophic larva. Results The character of foxA expression in the two polychaetes was similar but not identical. The genes were successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…In this type of healing, the severed gut edges also fuse, and a blind gut end forms [10,12]. In some cases of posterior regeneration, the severed edges of the epidermis and the gut epithelium fuse directly with each other and restore the anus by the wound healing process ("open regeneration" in nereids [34]).…”
Section: Early Events During Regeneration: Wound Healing and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In this type of healing, the severed gut edges also fuse, and a blind gut end forms [10,12]. In some cases of posterior regeneration, the severed edges of the epidermis and the gut epithelium fuse directly with each other and restore the anus by the wound healing process ("open regeneration" in nereids [34]).…”
Section: Early Events During Regeneration: Wound Healing and Immune Responsementioning
confidence: 99%
“…The wound epithelium is formed by the rearrangement of epithelial cells, but not by their active proliferation [36][37][38][39]. Transition to the next stage of regeneration, the blastema formation, is characterized by a sharp upregulation of cell proliferation and several genes known to be important developmental regulators [12,34,39]. After anterior and usually after posterior amputation, the wound heals by fusion of the severed edges of the epidermis over it.…”
Section: Early Events During Regeneration: Wound Healing and Immune Responsementioning
confidence: 99%
“…Regeneration has been studied mainly in Nereis virens (Holmes, 1931), Nereis diversicolor (Clark and Bonney, 1960), Owenia fusiformis (Coulon et al, 1989), Eurythoe complanata (Zapata-Vívenes, 2005), Dorvillea bermudensis (Paulus and Müller, 2006), Cirratulus cf. cirratus (Weidhase et al, 2014), Typosyllis antoni (Weidhase et al, 2017), Alitta virens (Kozin et al, 2017), and in P. dumerilii (Kostyuchenko et al, 2019). Collectively, these studies demonstrated that each specie present differences in its ability to regenerate.…”
Section: Annelidamentioning
confidence: 69%
“…One of the best developed models of segment recovery are nereid polychaetes, such as Alitta ( Nereis ), Platynereis and Perinereis . Their regeneration is predominantly epimorphic, with some substantial signs of morphallaxis [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%